Aplikasi Klinis Beberapa Trial Amiodaron - Yoga Yuniadi (The Indonesian Heart Association, 2009)
Amiodarone is a class-3 antiarrhythmia drug having a unique pharmaco-kinetic and pharmacodynamic properties. Some trials on amiodarone, from ARREST to ALIVE, showed its efficacy in acute phase or as chronic therapy of tachyarrhytmias. This article reviews clinical application of those trials.